Fill in the blanks to explain what needs to be done in the current step to get to the next step.

3x+4−2x+9=17−x
Step 1: 3x+4−2x+9=17−x


Step 2: x+13= 17−x


Step 3: x+x+13=17−x+x


Step 4: 2x +13 = 17


Step 5: 2x+13−13=17−13


Step 6: 2x=4


Step 7: x = 2

1 answer

Step 1: Simplify both sides of the equation by combining like terms.

Step 2: Add 'x' to both sides of the equation to isolate the variable on one side.

Step 3: Simplify further by combining like terms on both sides of the equation.

Step 4: Subtract 13 from both sides of the equation to isolate the variable 'x' on one side.

Step 5: Simplify further by combining like terms on both sides of the equation.

Step 6: Divide both sides of the equation by 2 to solve for 'x'.

Step 7: Simplify further to find the final solution for 'x'.